2020
DOI: 10.1111/psyg.12639
|View full text |Cite
|
Sign up to set email alerts
|

How have older adults reacted to coronavirus disease 2019?

Abstract: AimOutbreaks have a wide spectrum of psychosocial impact on individuals. This study aimed to investigate the psychosocial effects of measures to prevent the spread of the novel coronavirus disease on older adults in Turkey.MethodsA survey was conducted of 104 adults who had to stay at home during the pandemic. Participants’ depressive symptoms, anxiety symptoms, nutritional status, health‐related quality of life, and sleep quality were assessed.ResultsThe frequency of depressive and anxiety symptoms was 37.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 17 publications
2
23
1
6
Order By: Relevance
“…Ten papers were cross-sectional studies [21][22][23][24][25][26][27][29][30][31], and one was a retrospective longitudinal study [28].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten papers were cross-sectional studies [21][22][23][24][25][26][27][29][30][31], and one was a retrospective longitudinal study [28].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Ten of the included studies investigated factors associated with depression [21-30], six with anxiety [21,23,24,26,27,30], and one unified both psychological outcomes in a single variable expressed as "depression or anxiety" [31]. Additionally, one of the studies analysed the associations with comorbid depression and anxiety [26].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…During home confinement, the younger population reported lower sleep quality [13], increased occurrence of sleep problems [14,15], and worsening of existing sleep problems [14] compared to older people. Conversely, other investigations identified advanced age as a risk factor for sleep disturbances [16], being associated with a decline of sleep quality [17], especially in older individuals with depressive and anxiety symptoms [18]. A recent study also showed that older age represented a significant predictor of a higher association between sleep problems and psychological distress [19].…”
Section: Introductionmentioning
confidence: 96%